IS26-Flanked Composite Transposon Tn6539 Carrying the tet(M) Gene in IncHI2-Type Conjugative Plasmids From Escherichia coli Isolated From Ducks in China - Sun, Ya-wei; Liu, Ying-ying; Wu, Hua; Wang, Ling-fei; Liu, Jian-hua; Yuan, Li; Pan, Yu-shan; He, Dan-dan; Hu, Gong-zheng (Frontiers in Microbiology, 2019)
Tet(M)-type proteins confer resistance to tetracycline and related antibiotics by interacting with the ribosome. Genes encoding Tet(M) have been found in a range of bacteria, including Escherichia coli. In the current study, conjugation experiments were performed between seven different tetracycline-resistant, azide-susceptible E.coli strains isolated from ducks and tetracycline-sensitive, azide-resistant E.coli J53. Transconjugants were obtained from two of the strains at a frequency of 1.2×10-8. PCR, southern blotting and sequencing demonstrated that tet(M) in the transconjugants was located on a 50kb IncHI2-type plasmid and was part of a composite transposon, designated Tn6539. This transposon is flanked by two IS26 elements in opposite orientation and contains the Tn3△tnpA+△orf13-lp-tet(M)+gamma delta+tnpX+△tnpR sequences. The△orf13-lp-tet(M) sequence was a highly conserved genetic fragment in E.coli harboring tet(M) and mainly located in the composite transposons flanked by IS6-family elements. In summary, Tn6539 is a new composite transposon capable of horizontal transfer of tet(M) among E. coli isolates.